The Future of Learning is Hybrid: Exploration of EdTech's Role in Shaping the Post-Pandemic Educational Landscape - Sayed Mahbub Hasan Amiri; Prasun Goswami; Md. Mainul Islam; Mohammad Sohel Kabir; Mohammad Shakhawat Hossen (SocioEdu: Sociological Education, 2026)
The global COVID-19 pandemic acted as a profound catalyst, forcing an unprecedented and rapid shift to remote learning and exposing both the potential and the deep-seated vulnerabilities within global education systems. This paper argues that the post-pandemic educational landscape is irrevocably shifting towards a hybrid learning model, which integrates face-to-face instruction with technology-mediated learning experiences. This transition is not merely a temporary adjustment but a fundamental restructuring of pedagogical delivery, with Educational Technology (EdTech) at its core. The paper explores the dual role of EdTech as both an enabler of flexibility, personalization, and accessibility, and a potential amplifier of existing inequalities the "digital divide." Through a thematic analysis of recent literature, this study examines key themes, including the redefinition of teacher and student roles, the importance of digital pedagogy over mere tool usage, and the critical need for robust infrastructure and educator professional development. The conclusion posits that the successful implementation of a hybrid future is contingent upon a strategic, equitable, and pedagogically grounded integration of EdTech, moving beyond emergency remote teaching to create a more resilient, inclusive, and effective educational ecosystem.